2014
DOI: 10.1534/g3.113.009936
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Regulation of Bovine Monocyte Inflammatory and Metabolic Networks in anIn VivoInfection Model

Abstract: Bovine mastitis is an inflammation-driven disease of the bovine mammary gland that costs the global dairy industry several billion dollars per year. Because disease susceptibility is a multifactorial complex phenotype, an integrative biology approach is required to dissect the molecular networks involved. Here, we report such an approach using next-generation sequencing combined with advanced network and pathway biology methods to simultaneously profile mRNA and miRNA expression at multiple time points (0, 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 87 publications
6
78
0
1
Order By: Relevance
“…More identifications of the bovine miRNA expression atlas in different tissues and cells are necessary to further fill in the gap (Lawless et al . ,). These newly identified miRNAs could significantly expand the bovine miRNA spectrum and refine their annotations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More identifications of the bovine miRNA expression atlas in different tissues and cells are necessary to further fill in the gap (Lawless et al . ,). These newly identified miRNAs could significantly expand the bovine miRNA spectrum and refine their annotations.…”
Section: Resultsmentioning
confidence: 99%
“…Using next‐generation sequencing and RT‐PCR approaches, several studies have identified differentially expressed bovine miRNAs, target genes, KEGG pathways and related regulatory networks and pointed out their roles in regulating host response to S. aureus or Escherichia coli , in vivo and in vitro , at early stages of infection (Lawless et al . , ,; den Breems et al . ; Jin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Since BRD is a multi-factorial complex phenotype, dissecting molecular networks involved is essential for understanding the pathogenesis of BRD. It has been demonstrated that miRNAs play important roles in bovine monocyte inflammatory and metabolic networks (56). Many LPS-responsive miRNAs also have a role in proinflammatory cytokine production in other species rather than bovine (57-59).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have been shown to play roles in bovine infection and immunity in a wide range of tissues [54,[106][107][108][109][110][111][112][113]. For mammary gland, Naeem et al [114] studied the expression of 14 miRNAs (miR-10a, miR-15b, miR-16a, miR-17, miR-21, miR-31, miR-145, miR-146a, miR146b, miR-155, miR-181a, miR-205, miR-221 and miR-223) in MG tissue challenged with Streptococcus uberis and identified three downregulated miRNAs (miR-181a, miR-16 and miR-31) and one upregulated miRNA (miR-223) in infected versus healthy tissue.…”
Section: Microrna Functions In Mammary Gland Healthmentioning
confidence: 99%